Environmental Biotechnology : Principles and Applications - Rittmann, Bruce E.; McCarty, Perry L. (McGraw-Hill's AccessEngineering., 2018)
Environmental Biotechnology: Principles and Applications is the essential tool for understanding and designing microbiological processes used for environmental protection and improvement. The book lays a foundation in microbiology and engineering principles and provides comprehensive coverage of all the major environmental applications, from traditional ones like activated sludge and anaerobic digestion to emerging applications like detoxification of hazardous chemicals and biofiltration of drinking water. An abundance of worked examples that show in a step-by-step way how the tools are used in analysis and design enrich the discussion. Environmental Biotechnology is the authoritative source for learning how processes in environmental biotechnology work and how to create reliable processes to meet contemporary and emerging needs. Students, practitioners, and researchers will find this book invaluable.